2017
DOI: 10.1111/add.14076
|View full text |Cite
|
Sign up to set email alerts
|

The genetic and environmental architecture of substance use development from early adolescence into young adulthood: a longitudinal twin study of comorbidity of alcohol, tobacco and illicit drug use

Abstract: Among Norwegian adolescents, there appear to be strong genetic effects on both substance-specific and comorbid use of alcohol, illicit drugs and tobacco; individual differences in alcohol use can be explained partially by family background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 41 publications
0
9
0
2
Order By: Relevance
“…The plausibility of common factors underlying these bidirectional associations is supported by twin studies. Whereas some studies (Vrieze et al, 2012; Waaktaar et al, 2018) show that the comorbidity in youth tobacco use and substance use is largely due to a common genetic liability, other studies (Han et al, 1999; Koopmans et al, 1997) attribute the observed comorbidity to shared environmental factors. Therefore, consistent with an integrated risk-prevention perspective (Hale et al, 2014) our findings point to two promising directions for prevention and intervention efforts: (1) comprehensive screening of alcohol, tobacco, and any drug use among youth, and (2) addressing modifiable risk factors common to multiple forms of substance use.…”
Section: Discussionmentioning
confidence: 99%
“…The plausibility of common factors underlying these bidirectional associations is supported by twin studies. Whereas some studies (Vrieze et al, 2012; Waaktaar et al, 2018) show that the comorbidity in youth tobacco use and substance use is largely due to a common genetic liability, other studies (Han et al, 1999; Koopmans et al, 1997) attribute the observed comorbidity to shared environmental factors. Therefore, consistent with an integrated risk-prevention perspective (Hale et al, 2014) our findings point to two promising directions for prevention and intervention efforts: (1) comprehensive screening of alcohol, tobacco, and any drug use among youth, and (2) addressing modifiable risk factors common to multiple forms of substance use.…”
Section: Discussionmentioning
confidence: 99%
“…Twins provided self-reports, and parents of twins were asked to fill out the third-person version. That is, parents did not provide data about themselves (except a few demographic questions) but informant reports on each of their twin children (see also Waaktaar, Kan, & Torgersen, 2018).…”
Section: Participantsmentioning
confidence: 99%
“…Çalışmamızda sağlıklı kontrollerde evli olma oranının daha yüksek olması literatürle uyumluluk göstermektedir. Madde kullanımının boşanma, ayrılma ve evli kalmamayla ilişkili olduğu birçok çalışmada bildirilmektedir (34)(35)(36). Eğitim durumunun düşüklüğü meslek sahibi olmamak, çalışmamak, serbest meslek icra etmek veya özel sektörde çalışmak, düşük gelir düzeyine sahip olmak gibi değişkenleri de yakından etkilemektedir.…”
Section: Discussionunclassified